Euselasia hygenius Occulta (Riodininae): First report of feeding on Psidium guajava (Myrtaceae) in Minas Gerais State, Brazil - Zanuncio, José Cola; Soares, Marcus Alvarenga; Zanuncio, Teresinha Vinha; Mielke, Olaf Hermann Hendrik; De Sousa Ramalho, Francisco; De Assis Júnior, Sebastiao Lourenço; Wilcken, Carlos Frederico [UNESP] (My University, 2013)
Insect defoliators of native Myrtaceae in Brazil are important because of potential outbreaks in reforestation of exotic Eucalyptus spp. The objective of this study was to identify a lepidopteran defoliator of Psidium guajava (Myrtaceae) found at the Federal University of Viçosa in Viçosa, Minas Gerais, Brazil. Insects were identified as Euselasia hygenius occulta Stichel 1919 (Lepidoptera: Riodininae). Larvae of this insect are gregarious and feed, rest, molt, and pupate synchronously. This species exhibits processionary behavior during its five instars. Caterpillars are yellow in the first instar and dark brown in the last one with six longitudinal white stripes, two on the back, and two on each side. Head of caterpillars is orange in color and the body has multiple setae per segment. Adults of this species have sexual dimorphism with females having a pale gray dorsal tinge, a darker gray ventral coloration and a 2.5 cm wingspan Males are dark gray ventrally and black dorsally with a 2.7 cm wingspan. The head of both sexes has a V shape when viewed from the front. Euselasia hygenius occulta should be included in monitoring programs of P. guajava pests, its native host, and also on those of Eucalyptus spp. due to the apparent palatability of these nonnative plants.
Keywords: Caterpillars; Eucalyptus; Lepidoptera